قانون منع إساءة استعمال أجهزة الاتصالات في إقليم كوردستان العراق : دراسة فقهية تقويمية - أحمد، كوسرت صالح (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2015)
The objective of this research is to study the law on the prevention of abuse of the communicative devices in the Kurdistan-region of Iraq, as this law suffers from serious problems, some of which are due to the legislative drafting on the grounds that this law has legal loopholes, legislative errors as well as linguistic errors. Other issues are related to legislative shortcomings, or not addressing the criminalization of certain illicit activities done by the communicative devices. The researcher sought to resolve these issues in light of Islamic jurisprudence through studying the legal loopholes and legislative shortcomings of the law. In addition, he pursued finding Islamic legal solutions to these problems. The researcher adopted the inductive method via the extrapolation and the tracking-down of Islamic jurisprudence on the penalties for the perpetrators of these crimes in connection with communicative devices within the contemporary Islamic criminal jurisprudence; he also referred to the sayings of scholars and legal contemporary experts and researchers in this regard. Another approach adopted by the researcher was the analytical method by exposing the theme of the abuse of communicative devices which transgresses on the sanctity and rights of others, the ensued sanctions stated in the law of the Kurdistan-region of Iraq and their equivalence in contemporary Islamic jurisprudence. The researcher then made an assessment of the sanctions contained in the law in light of Islamic jurisprudence backed by objective evidence. Amongst the most important findings is that the enactment of this law is an important practical step in the process of protecting the rights inherent in the communicative devices. Albeit the law came to fill a legal vacuum and legislative shortage in the field of telecommunications and electronics crimes, it is nevertheless a flawed legislation. In order to achieve the law's objectives in deterrence and reform, the researcher proposes modifying it as soon as possible so as to amend most of its provisions and add other texts, particularly with regard to the criminalization of eavesdropping on those devices and bugging in order to save the inviolability of private life and not violate it with communicative devices and modern technology.